SIPENMA: Pemodelan UML dan Uji BlackBox pada Perancangan Sistem Pendaftaran Magang - Naryama Harahap; Muhammad Dedi Irawan; Yusuf Hanifiah (Program Studi Sistem Informasi, 2022)
North Sumatra Ministry of Industry and Trade is a government agency as the executor of regional government affairs which has the task of decentralization and deconcentration, especially in the industrial and trade fields as well as other auxiliary tasks assigned by the governor. In this agency internship acceptance activity still uses manual method, to overcome this problem, an internship registration system is needed to make it easier to register for internships. This study uses the waterfall method, UML, and testing using Blackbox. The result of this study is design of the internship registration system (SIPENMA) which makes it easy to register for internships via the web and can be accessed at any time. Keywords: SIPENMA, UML, Blackbox, Waterfall